Haemolaelaps Berlese removed from synonomy with Androlaelaps Berlese (Acari: Laelapidae) - Shaw, Matthew D. (Zootaxa, 2014)
Comparison of species of Androlaelaps with all members of the Haemolaelaps marsupialis group show these to be two consistently distinct groups. Haemolaelaps is removed from synonomy with Androlaelaps and rediagnosed. A close relationship between Peramelaelaps Womersley and Haemolaelaps is proposed.